Community-acquired bacterial meningitis in adults in the Netherlands, 2006–14: a prospective cohort study. Issue 3 (March 2016) - Bijlsma, Merijn W; Brouwer, Matthijs C; Kasanmoentalib, E Soemirien; Kloek, Anne T; Lucas, Marjolein J; Tanck, Michael W; van der Ende, Arie; van de Beek, Diederik
Summary: Background: We studied causative pathogens, clinical characteristics, and outcome of adult community-acquired bacterial meningitis after the introduction of adjunctive dexamethasone treatment and nationwide implementation of paediatric conjugate vaccines. Methods: In this cohort study, we prospectively assessed adults (age >16 years) with community-acquired bacterial meningitis in the Netherlands, identified through the National Reference Laboratory for Bacterial Meningitis or individual physicians between Jan 1, 2006, and July 1, 2014. We identified independent predictors of an unfavourable outcome (Glasgow Outcome Scale score 1–4) by logistic regression. Findings: We assessed 1412 episodes of community-acquired bacterial meningitis. Incidence declined from 1·72 cases per 100 000 adults per year in 2007–08, to 0·94 per 100 000 per year in 2013–14. Streptococcus pneumoniae caused 1017 (72%) of 1412 episodes. Rates of adult bacterial meningitis decreased most sharply among pneumococcal serotypes included in paediatric conjugate vaccine, and in meningococcal meningitis. We found no evidence of serotype or serogroup replacement. The overall case fatality rate was 244 (17%) of 1412 episodes and unfavourable outcome occurred in 531 (38%) of 1412 episodes. Predictors of unfavourable outcome were advanced age, absence of otitis or sinusitis, alcoholism, tachycardia, lower score on the Glasgow Coma Scale, cranial nerve palsy, a cerebrospinal fluid white-cell count lower than 1000 cells per μL, a positive blood culture, and a high serum C-reactive protein concentration. Adjunctive dexamethasone was administered for 1234 (89%) of 1384 assessed episodes. The multivariable adjusted odds ratio of dexamethasone treatment for unfavourable outcome was 0·54 (95% CI 0·39–0·73). Interpretation: The incidence of adult bacterial meningitis has decreased substantially, which is partly explained by herd protection by paediatric conjugate vaccines. Adjunctive dexamethasone treatment was associated with substantially improved outcome. Funding: European Research Council, National Institute of Public Health and the Environment, European Union, Academic Medical Center, and Netherlands Organization for Health Research and Development.